Evaluation of the Efficiency of a Septic Tank Combined with Anaerobic Filter, Filled with Plastic Residue, Including a Root Zone - Lira, Vivian Silva; Freire, Alice Gabriela; Fracácio, Renata; Morais, Leandro Cardoso (Fronteira: Journal of Social, Technological and Environmental Science, 2020)
Considering the damages resulting from the dumping of waste in natura in the bodies of water and soil, an alternative system of treatment of domestic effluent with septic tank and an anaerobic filter was installed, following a root zone. The evaluation of the efficiency of the system was based on analyzes of the physical, chemical, biological variables and ecotoxicological tests (toxicity tests with Ceriodaphnia dubia). The conductivity values decreased after treatment (83.4%), from 3380 to 561 ÂµS cm-1. The average efficiency of removal of organic matter was 88.75% and there was a significant decrease in BOD. The removal of phosphorus was 97.68% and nitrogen was 94.7%. The toxicity tests determined an LC50 = 1.70% for the raw effluent and in the treated effluent, an LC50 = 16.63%. The system achieved good efficiency in the reduction of all analyzed parameters. The use of a plastic residue as a filter element has proved quite feasible.